Efficient molecular ferroelectric photovoltaic device with high photocurrent via lewis acid–base adduct approach. (1st October 2022) - Gu, Jiahao; Wang, Chen; Xu, Xiaoli; Xiao, Lingbo; Li, Jun; Zhao, Jie; Zou, Guifu
Abstract: Traditional inorganic oxide ferroelectric materials usually have band gaps above 3 eV, leading to more than 80% of the solar spectrum unavailable, greatly limiting the current density of their devices just at μ A cm −2 level. Therefore, exploring ferroelectric materials with lower band gaps is considered as an effective method to improve the performance of ferroelectric photovoltaic devices. Inorganic ferroelectric materials are often doped with transition metal elements to reduce the band gap, which is a complex doping and high temperature fabrication process. Recently, molecular ferroelectric materials can change the symmetry and specific interactions of crystals at the molecular level by chemically modifying or tailoring cations with high symmetry, enabling rational design and banding of ferroelectricity in the framework of perovskite simultaneously. Therefore, the molecular ferroelectric materials have a great performance for both excellent ferroelectricity and narrow band gap without doping. Here, we report a ferroelectric photovoltaic device employing an organic-inorganic hybrid molecular ferroelectric material with a band gap of 2.3 eV to obtain high current density. While the poor film quality of molecular ferroelectrics still limits it. The Lewis acid–base adduct is found to greatly improve the film quality with lower defect density and higher carrier mobility. Under standard AM 1.5 G illumination, the photocurrents of ∼1.51 mA cm −2 is achieved along with a device efficiency of 0.45%. This work demonstrates new possibilities for the application of molecular ferroelectric films with narrow band gaps in photovoltaic devices, and lays a foundation for Lewis acid–base chemistry to improve the quality of molecular ferroelectric thin films to obtain high current densities and device performance.